An evaluation of the effect of an angiotensin-converting enzyme inhibitor on the growth rate of small abdominal aortic aneurysms: a randomized placebo-controlled trial (AARDVARK) - Bicknell, Colin D.; Kiru, Gaia; Falaschetti, Emanuela; Powell, Janet T.; Poulter, Neil R. (European heart journal, 2016)
The AARDVARK (Aortic Aneurysmal Regression of Dilation: Value of ACE-Inhibition on RisK) trial investigated whether ACE-inhibition reduces small abdominal aortic aneurysms (AAA) growth rate, independent of blood pressure (BP) lowering. A three-arm, multi-centre, single-blind, and randomized controlled trial (ISRCTN51383267) was conducted in 14 hospitals in England. Subjects aged ≥55 years with AAA diameter 3.0-5.4 cm were randomized 1:1:1 to receive perindopril arginine 10 mg, or amlodipine 5 mg, or placebo and followed 3-6 monthly over 2 years. The primary outcome was aneurysm growth rate (based on external antero-posterior ultrasound measurements in the longitudinal plane), determined by multi-level modelling to provide maximum likelihood estimates. Two hundred and twenty-four subjects were randomized (2011-2013) to placebo (n = 79), perindopril (n = 73), or amlodipine (n = 72). Mean (SD) changes in mid-trial systolic BP (12 months) were 0.5 (14.3) mmHg, P = 0.78 compared with baseline, -9.5 (13.1) mmHg (P < 0.001), and -6.7 (12.0) mmHg (P < 0.001), respectively. No significant differences in the modelled annual growth rates were apparent [1.68 mm (SE 0.2), 1.77 mm (0.2), and 1.81 mm (0.2), respectively]. The estimated difference in annual growth between the perindopril and placebo groups was 0.08 mm (CI -0.50, 0.65). Similar numbers of AAAs in each group reached 5.5 cm diameter and/or underwent elective surgery: 11 receiving placebo, 10 perindopril, and 11 amlodipine. Small AAA growth rates were lower than anticipated, but there was no significant impact of perindopril compared with placebo or placebo and amlodipine, combined despite more effective BP lowering.